Pengaruh Citra Merek, Kualitas Produk Dan Persepsi Harga Terhadap Keputusan Pembelian Di Kopi Nusa - Bima Aji Saputra; Rully Arifiansyah (CV. ULIL ALBAB CORP, 2024)
This research aims to determine and analyze the influence of brand image, product quality, and price perception on purchasing decisions at Kopi Nusa. The population in this study were Kopi Nusa customers with samples taken using accidental sampling. Data collection was carried out accidentally using a questionnaire that had been tested for validity and reliability. The analytical method used is the classic test, before multiple linear regression with SPSS 25. 100 respondents were used as a tool, followed by the F, t, correlation and determination tests. The results of this research prove that partially, the brand image variable has no significant effect on purchasing decisions, the product quality variable has a significant effect on purchasing decisions, and the price perception variable has a significant effect on purchasing decisions. Therefore, the variables of brand image, product quality, and price perception simultaneously influence purchasing decisions.